Menerapkan Kebenaran Dalam Kepemimpinan Menurut 1 Timotius bagi Pengurus di GBI Bethel Bandung - Senjaya, Styadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Abstract The Christian view of leadership which emphasizes age and gender has become a problem in church organization. Because at this time, leadership needs to emphasize the competencies possessed by a leader. Young people also need to be given the opportunity to be a space for them to innovate in every decision made in church organization. When young people are included and involved there will be rapid growth. Like what the Bible says in 1 Timothy 4:12 what Paul did to Timothy provides a picture for church leaders today to give trust to young people. This study uses a literature study approach. So that it takes out every existing fact to bring out the best essence. In the end, it can be proven that the role model of young people is one of the most important competencies possessed by young leaders.